2005
DOI: 10.1002/pbc.20471
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate induces cell swelling and necrosis in renal tubular cells

Abstract: MTX induces cell swelling and cell death in renal tubular LLC-PK(1) cells. The tubular cell death induced by MTX is time-dependent. Cell death can be prevented by co-incubating with amiloride, thus indicating that the Na(+)/H(+) antiporter and possibly other volume regulatory factors in renal tubular cells are involved in MTX-induced renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
2
20
0
1
Order By: Relevance
“…The results showed that MTX caused oxidative renal tissue damage, as evidenced by renal histopathological findings in the form of tubular distension, interstitial inflammation, perirenal inflammation, glomerular congestion, glomerular degeneration, parenchymal hemorrhage, and perirenal eosinophil infiltration, which is in agreement with the findings of previous studies [35][36][37]. Pretreatment with HLX before the administration of MTX ameliorated the MTX-induced damage of the kidneys.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results showed that MTX caused oxidative renal tissue damage, as evidenced by renal histopathological findings in the form of tubular distension, interstitial inflammation, perirenal inflammation, glomerular congestion, glomerular degeneration, parenchymal hemorrhage, and perirenal eosinophil infiltration, which is in agreement with the findings of previous studies [35][36][37]. Pretreatment with HLX before the administration of MTX ameliorated the MTX-induced damage of the kidneys.…”
Section: Discussionsupporting
confidence: 82%
“…Each criterion was scored (1 score per rat) using a semiquantitative scale as follows: 0 = none, 1 = mild, 2 = moderate, 3 = severe [35][36][37].…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Elevation in plasma MTX levels can lead to enhancement of MTX's other toxicities [1,3] . Routine monitoring of serum creatinine and MTX is being done for management of MTX-induced renal dysfunction [18] . The pathogenesis of MTX-induced renal dysfunction is not clear, although it is believed to be mediated via the precipitation of MTX and its metabolites in the renal tubules [19,20] or by a direct toxic effect of MTX on the renal tubules [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The software used was created by one of the authors (A.e.) and it is part of the software currently used at the image analysis core facility of the Department of Pathology, Karolinska University Hospital/Karolinska Institutet, Stockholm (14). Results were analysed using the STATISTICA software.…”
Section: Mathematical Determination Of Positivity In Immunohistochemimentioning
confidence: 99%
“…In the case of ERdj5, there was very high expression compared to internal control specifically located to the cytosol of the tumor cells of all patient cases. To measure and compare the different degrees of positivity of the expression patterns of the thioredoxin family proteins, we developed a system based on the evaluation of the saturation of the IHC staining of the tumor tissue compared to the non-tumor tissue of the same section (14). Comparisons within the same sections are the ideal internal control as both were treated exactly the same throughout the entire process from fixation to staining.…”
Section: Immunohistochemistry Ofhuman Hepatocellular Carcinoma Sectionsmentioning
confidence: 99%